Advances in mesenchymal stem cell transplantation for the treatment of osteoporosis. (18th November 2020) - Jiang, Yuhe; Zhang, Ping; Zhang, Xiao; Lv, Longwei; Zhou, Yongsheng
Abstract: Osteoporosis is a systemic metabolic bone disease with characteristics of bone loss and microstructural degeneration. The personal and societal costs of osteoporosis are increasing year by year as the ageing of population, posing challenges to public health care. Homing disorders, impaired capability of osteogenic differentiation, senescence of mesenchymal stem cells (MSCs), an imbalanced microenvironment, and disordered immunoregulation play important roles during the pathogenesis of osteoporosis. The MSC transplantation promises to increase osteoblast differentiation and block osteoclast activation, and to rebalance bone formation and resorption. Preclinical investigations on MSC transplantation in the osteoporosis treatment provide evidences of enhancing osteogenic differentiation, increasing bone mineral density, and halting the deterioration of osteoporosis. Meanwhile, the latest techniques, such as gene modification, targeted modification and co‐transplantation, are promising approaches to enhance the therapeutic effect and efficacy of MSCs. In addition, clinical trials of MSC therapy to treat osteoporosis are underway, which will fill the gap of clinical data. Although MSCs tend to be effective to treat osteoporosis, the urgent issues of safety, transplant efficiency and standardization of the manufacturing process have to be settled. Moreover, a comprehensive evaluation of clinical trials, including safety and efficacy, is still needed as an important basis for clinical translation. Abstract : Osteoporosis occurs when the orchestrated balance between bone formation by osteoblasts and bone destruction by osteoclasts breaks down, and this process is closely associated with MSCs. Existing preclinical evidences of MSCs derived from different tissues support MSCs‐based cell therapy as a possible radical approach to the prevention and treatment of osteoporosis. Clinical trials of MSC transplantation for osteoporosis mainly focus on the application of autologous cells and will fill the gap of clinical data.